Towards the Development of an Aptamer-based Polymeric Biosensor for Biomolecular Screening - Acquah, Caleb (Curtin University, 2017)
This thesis reports the development and characterization of a multifunctional miniaturized polymeric biosensor for rapid bioscreening applications. The functional features of the device is based on the highly selective affinity binding characteristics of aptamer molecules and the convective fluid mass transfer properties of monolithic polymers. This combination creates the capacity to specifically identify and isolate biomolecules in real time with potential applications for high throughput pathogen detection and biomolecular purification.